The Optimization of Ti Gradient Porous Structure Involves the Finite Element Simulation Analysis - Liu, Bowen; Xu, Wei; Lu, Xin; Tamaddon, Maryam; Chen, Mingying; Dong, Jiaqi; Liu, Yitong; Guo, Lijia; Zhang, Jiazhen; Qu, Xuanhui; He, Xinbo; Liu, Chaozong (Frontiers in Materials, 2021)
Titanium (Ti) and its alloys are attracting special attention in the field of dentistry and orthopaedic bioengineering because of their mechanical adaptability and biological compatibility with the natural bone. The dental implant is subjected to masticatory forces in the oral environment and transfers these forces to the surrounding bone tissue. Therefore, by simulating the mechanical behavior of implants and surrounding bone tissue we can assess the effects of implants on bone growth quite accurately. In this study, dental implants with different gradient pore structures that consisted of simple cubic (structure a), body centered cubic (structure b) and side centered cubic (structure c) were designed, respectively. The strength of the designed gradient porous implant in the oral environment was simulated by three-dimensional finite element simulation technique to assess the mechanical adaptation by the stress-strain distribution within the surrounding bone tissue and by examining the fretting of the implant-bone interface. The results show that the maximum equivalent stress and strain in the surrounding bone tissue increase with the increase of porosity. The stress distribution of the gradient implant with a smaller difference between outer and inner pore structure is more uniform. So, a-b type porous implant exhibited less stress concentration. For a-b structure, when the porosity is between 40% and 47%, the stress and strain of bone tissue are in the range of normal growth. Based on the simulated results, to achieve an improved mechanical fixation of the implant, the optimum gradient porous structure parameters should be: average porosity 46% with an inner porosity of 13% (b structure) and outer porosity of 59% (a structure), and outer pore sized 500 μm. With this optimized structure, the bone can achieve optimal ingrowth into the gradient porous structure, thus provide stable mechanical fixation of the implant. The maximum equivalent stress achieved 99 MPa, which is far below the simulation yield strength of 299 MPa.